Balanga sebagai Artefak Keramik Warisan Budaya dalam Perspektif Budaya Material Masyarakat Dayak Palangka Raya - Muhamad Romadoni; Muh. Andis Hidayatullah; Nawung Asmoro Girindraswari (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Balanga is a traditional ceramic artifact that plays an important role in the social and cultural life of the Dayak people of Palangka Raya, Central Kalimantan. However, studies of traditional ceramics in Indonesia have so far focused more on aspects of technology, style, and history, so that understanding of Balanga as an active cultural agent in the perspective of material culture is still limited. This condition has implications for the marginalization of the role of artifacts in shaping social relations, visual meaning production, and cultural identity dynamics in material culture, design, and visual anthropology studies in Indonesia. This study aims to reveal the relationship between the material aspects, social functions, and symbolic meanings of Balanga as cultural heritage artifacts in the daily practices of the Dayak community. This study uses a qualitative approach based on material culture theory, supported by artifact analysis and semiotic interpretation. Data were collected through field observations, in-depth interviews with traditional leaders and cultural practitioners, as well as documentation of Balanga owned by the community and museum collections. The results of the study show that Balanga not only functions as a utilitarian ceramic container, but also as a ritual object, family heirloom, and a marker of social identity and collective memory. The material characteristics of Balanga reflect a mature mastery of traditional ceramic technology, while its decorative motifs, especially the dragon motif, represent symbolic meanings that are formed through negotiations between